DINAMIKA POPULASI GULMA PADA PERTANAMAN SEMANGKA(Citrulus vulgaris Schard)DARI PENGARUH DOSIS KALIUM YANG BERBEDA PADA TANAH ULTISOL - Syahpiri, Marizan; Suzanna, Eka; Anwar, Risvan; Aryani, Farida (University of Prof. Dr. Hazairin, SH, 2024)
This research aims to determine the effect of potassium fertilizer doses on the growth and yield of watermelon plants planted in ultisol soil, and determine short-term changes in weed composition.The experiment used a Randomized Block Design (RAK) with five treatments of potassium (D) doses and three replications. The treatment doses are: Without fertilizer (control) equivalent to 0 kg/plot; A dose of 125 kg/ha is equivalent to 37.4 g/plot; A dose of 250 kg/ha is equivalent to 74.8 g/plot; A dose of 375 kg/ha is equivalent to 112.1 g/plot; A dose of 500 kg/ha is equivalent to 149.5 g/plot. The research data was analyzed using Sidik Ragam to find out whether the treatment had a real effect or an insignificant effect. If the results of the analysis have a real or very real effect, then continue with the Duncant's Multiple Range Test (DMRT) at the 5% level.This research concluded: (1) The dose of potassium fertilizer had no significant effect on plant length and fruit weight per plant but had a very significant effect on fruit weight per plot. Potassium fertilizer dose of 500 kg/ha provides the highest fruit weight per plot; (2) Potassium fertilizer doses tend to provide different weed populations and dry weights in watermelon plantings. The higher the dose of potassium fertilizer given tends to increase the weed population and weed dry weight; (3) The weed community coefficient index between mid and late weeds in watermelon planting is the same. However, the number of weed populations and biomass in the middle observation was higher than the final observation of watermelon planting.